Inhibición de Crecimiento de Tumores de Cáncer de Próstata en Hipertermia Magnética mediada por Nanopartículas en Estudios Preclínicos: una Revisión de Alcance: Prostate Cancer Tumor Growth Inhibition in Nanoparticle mediated Magnetic Hyperthermia on Preclinical trials: a Scoping Review - Parada Peralta, José Agustín; Chapa González, Christian (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Prostate Cancer is one of the major concern types of cancer among men with respect to incidence and mortality. One relatively recent therapy against it, provided by Nanomedicine, is Nanoparticle mediated Magnetic Hyperthermia, which consists on tumor heating when exposed to an Alternating Magnetic Field in order to inhibit tumor growth (around 42 °C) (and make tumor sensible to other therapies: synergia) or to cause cancer cell apoptosis (greater temperature than 42°C). This procedure has several advantages like deep-tissue-penetration, targeted heating, low toxicity by Nanoparticles, and others. To this treatment, some of the Magnetic Nanoparticle properties are fundamental to its success, principaly the size, morphology, etc. Here, therefore, the relationship between the size of the employed Nanoparticles and the Tumor Growth Inhibition that cause is reviewed when treating Prostate Cancer tumors on mice models by Magnetic Hyperthermia.